1997
DOI: 10.1084/jem.186.1.25
|View full text |Cite
|
Sign up to set email alerts
|

The Central Executioner of Apoptosis: Multiple Connections between Protease Activation and Mitochondria in Fas/APO-1/CD95- and Ceramide-induced Apoptosis

Abstract: According to current understanding, cytoplasmic events including activation of protease cascades and mitochondrial permeability transition (PT) participate in the control of nuclear apoptosis. However, the relationship between protease activation and PT has remained elusive. When apoptosis is induced by cross-linking of the Fas/APO-1/CD95 receptor, activation of interleukin-1β converting enzyme (ICE; caspase 1) or ICE-like enzymes precedes the disruption of the mitochondrial inner transmembrane potential (ΔΨm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
429
2
3

Year Published

1998
1998
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 606 publications
(455 citation statements)
references
References 49 publications
21
429
2
3
Order By: Relevance
“…The amount of the active cleaved form of caspase-2 was maximum after 24 h and it disappeared after 48 h. In contrast, the p17 and p19 forms of caspase-3 were apparent 24 h after stimulation with TGFb and the active p17 form, but not the p19 form, was present after 48 h. This di erent kinetics suggested that TGFb could activate a cascade of di erent caspases similar to that described for Fas-mediated apoptosis (Hirata et al, 1998;Kamada et al, 1997;Susin et al, 1997). However, we were not able to detect, by Western blotting, expression of either proforms or active proteolytic fragments of caspases-1, 4, 6 or 7 in BL41 cells after 30 min and 48 h of activation by TGFb (data not shown).…”
Section: Discussionmentioning
confidence: 87%
“…The amount of the active cleaved form of caspase-2 was maximum after 24 h and it disappeared after 48 h. In contrast, the p17 and p19 forms of caspase-3 were apparent 24 h after stimulation with TGFb and the active p17 form, but not the p19 form, was present after 48 h. This di erent kinetics suggested that TGFb could activate a cascade of di erent caspases similar to that described for Fas-mediated apoptosis (Hirata et al, 1998;Kamada et al, 1997;Susin et al, 1997). However, we were not able to detect, by Western blotting, expression of either proforms or active proteolytic fragments of caspases-1, 4, 6 or 7 in BL41 cells after 30 min and 48 h of activation by TGFb (data not shown).…”
Section: Discussionmentioning
confidence: 87%
“…There are numerous studies suggesting that overexpression of Bcl-2 or Bcl-x L can block apoptosis by effects at the mitochondrion (Shimizu et al, 1996;Susin et al, 1997;Yang et al, 1997), whereas Bax and Bak have been shown to exert pro-apoptotic activity (Chittenden et al, 1995;Narita et al, 1998). We examined the effect of STS on the expression levels of Bcl-2, Bcl-x L, Bak and Bax proteins.…”
Section: Effect Of Staurosporine On Bcl-2 Bcl-x L Bak and Bax Proteimentioning
confidence: 99%
“…Apoptosis has been shown to trigger mitochondrial permeability transition (Susin et al, 1997) as well as mitochondrial release of pro-apoptotic factors (Susin et al, 1996;Kluck et al, 1997;Yang et al, 1997). To detect the modi®cations of the mitochondrial membrane potential, we treated mock-transfected and p27 Kip1 -overexpressing cells with 50 mM etoposide for indicated times.…”
Section: P27 Kip1 Overexpression Delays Mitochondrial Changes Associamentioning
confidence: 99%